Influence and Potential of Additive Manufactured Reference Geometries for Ultrasonic Testing - Stefan Keuler; Anne Jüngert; Martin Werz; Stefan Weihe (Journal of Manufacturing and Materials Processing)
This study researches and discusses the impact of different manufacturing-induced effects of additive manufacturing (AM), such as anisotropy on sound propagation and attenuation, on the production of test specimens for ultrasonic testing (UT). It was shown that a linear, alternating hatching pattern led to strong anisotropy in sound velocity and attenuation, with a deviation in sound velocity and gain of over 840 m/s and 9 dB, depending on the measuring direction. Furthermore, it was demonstrated that the build direction exhibits distinct acoustic properties. The influence of surface roughness on both the reflector and coupling surfaces was analyzed. It was demonstrated that post-processing of the reflector surface is not necessary, as varying roughness levels did not significantly change the signal amplitude. However, for high frequencies, pre-treatment of the coupling surface can improve sound transmission up to 6 dB at 20 MHz. Finally, the reflection properties of flat bottom holes (FBH) in reference blocks produced by AM and electrical discharge machining (EDM) were compared. The equivalent reflector size (ERS) of the FBH, which refers to the size of an idealized defect with the same ultrasonic reflection behavior as the measured defect, was determined using the distance gain size (DGS) method—a method that uses the relationship between reflector size, scanning depth, and echo amplitude to evaluate defects. The findings suggest that printed FBHs achieve an improved match between the ERS and the actual manufactured reflector size with a deviation of less than 13%, thereby demonstrating the potential for producing standardized test blocks through additive manufacturing.